Effect of sintering temperature on the accuracy of MIM small-module gears - LIU Zuoshi; MING Aoyang; REN Jihua; WANG Xiaoyi; ZHONG Zhicheng; ZHU Minfeng; ZHU Weidong (Jixie chuandong)
ObjectiveIn order to improve the accuracy of small-module gears, small-module gears are prepared by using 420 stainless steel powder as raw material and metal powder injection molding (MIM) process at a sintering temperature of 1 330-1 360 ℃. The injection blank with the best micro-morphology was taken as a prerequisite to study the effect of sintering temperature on the accuracy of small-module gears.MethodsMLA650F field emission scanning electron microscope was used to observe the microscopic morphology of the gear injection blanks; JE 20 gear measuring center, Image J software, and Rockwell hardness tester were used to measure the accuracy, porosity, and hardness of the sintered gears, respectively.ResultsThe results show that under 110 MPa injection pressure, in the sintering temperature range of 1 330-1 350 ℃, the porosity of the gear surface decreases by 48.28%, the density increases by 5%, the hardness increases by 8.22%, the shrinkage continues to increase, and the accuracy is gradually improved; when the temperature is more than 1 350 ℃, the porosity decreases by 20%, the density decreases by 0.26%, the hardness decreases by 0.51%, the shrinkage rate increases slowly, and the accuracy of the gear gradually decreases; when the sintering temperature is 1 350 ℃, the gear has the best comprehensive performance, with a porosity of 1.5%, a density of 7.56 g/cm3, a hardness of 39.5 HRC, a shrinkage rate of 14.1%, and the highest accuracy level of grade 7 in the GB/T 2363—1990 testing standards.